Hyperglycaemia is associated with impaired pulsatile insulin secretion: effect of basal insulin therapy. Issue 3 (28th January 2013) - Meier, J. J.; Pennartz, C.; Schenker, N.; Menge, B. A.; Schmidt, W. E.; Heise, T.; Kapitza, C.; Veldhuis, J. D.
<x xml:space="preserve">Abstract</x> Aim Postprandial insulin pulsatility is impaired in patients with type 2 diabetes, but the effects of exogenous insulin therapy on pulsatile insulin secretion are not known. We addressed, whether pulsatile insulin secretion is related to glycaemic control, whether basal insulin supplementation increases postprandial insulin secretion, and if so, is this accomplished by a specific improvement in pulsatile insulin secretion? Methods Fourteen patients with type 2 diabetes underwent a mixed meal test before and after an 8‐week treatment period with insulin glargine. Glucose, insulin and C‐peptide levels were measured, and insulin pulsatility was determined by deconvolution analysis. Results Insulin treatment lowered fasting glycaemia from 179.6 ± 7.5 mg/dl to 117.6 ± 6.5 mg/dl (p < 0.001). Postprandial insulin and C‐peptide levels increased significantly after the treatment period (p < 0.0001). The total calculated insulin secretion rate increased with insulin treatment (p = 0.0039), with non‐significant increases in both pulsatile and non‐pulsatile insulin secretion. Insulin pulse frequency was unchanged by the intervention. There was an inverse relationship between fasting and postprandial glycaemia and insulin pulse mass (r2 = 0.51 and 0.56, respectively), whereas non‐pulsatile insulin secretion was unrelated to either fasting or postprandial glucose concentrations (r2 = 0.0073 and 0.031). Conclusions Hyperglycaemia in type 2 diabetes is associated with a reduction in postprandial insulin secretion, specifically through a reduction in insulin pulsatility. Reducing chronic hyperglycaemia by basal insulin therapy enhances endogenous β‐cell function in the postprandial state. These data support the use of basal insulin regimens in the pharmacotherapy of overtly hyperglycaemic patients with type 2 diabetes.